Analysis of the Financial Literacy Level of PKH Recipients and Its Impact on Family Financial Management: Analisis Tingkat Literasi Keuangan Penerima PKH dan Dampaknya pada Pengelolaan Keuangan Keluarga - Melizubaida Mahmud; Yulianti Tolarawe; Risca Marsanti Halid; Neva Lionitha Ibrahim (Universitas Muhammadiyah Sidoarjo, 2026)
This study aims to analyse the influence of financial literacy on household financial management and to examine differences in financial management based on literacy levels among beneficiaries of the Family Hope Programme (PKH) in Botubarani Village. This study employs a quantitative approach with a causal-comparative design and involves 60 respondents from a total population of 242 PKH beneficiaries. Data analysis was conducted using ANOVA, post hoc Games-Howell tests, and simple linear regression. The results indicate a significant difference in financial management based on financial literacy levels (F = 11.419; p < 0.001). The ‘well-literate’ group demonstrated better financial management skills compared to the ‘sufficiently literate’ and ‘less literate’ groups. Furthermore, financial literacy had a positive and significant effect on financial management (t = 4.816; p < 0.001), accounting for 28.6% of the variance. This study contributes by demonstrating that financial literacy not only has a general influence but also serves as a distinguishing factor among groups of social assistance recipients in rural areas. The implications of this study emphasise the importance of mentoring-based financial literacy education to enhance the effectiveness of the PKH programme and the financial independence of the community.